CHALLENGES OF MANAGING SYSTEMIC INFECTIONS IN HEALTHCARE SETTINGS ASSOCIATED WITH HOSPITALIZED PATIENTS UNDERGOING INVASIVE PROCEDURES - Fagundes, Pamella Dalgobbo Duque Estrada; Viana, Giuliane Ribeiro; Pessoa, Nicolly da Silva; da Rocha, Natacha Dalis Gomes; Peixoto, Francisco Dieiemes Alves; da Silva, Gilson Viana; de Souza, Cassius (Seven Editora, 2025)
The use of central venous catheters in hospitals is intended to help treat critically ill patients. However, this device can often cause bloodstream infections and adverse health reactions. According to the National Health Surveillance Agency (ANVISA), central venous catheters are classified as short and long stay. They can also be classified as semi-implantable and fully implantable (BRASIL, 2010). The use of inadequate practices in the insertion and maintenance of central venous catheters in patients can contribute to an increase in infections. Carrying out preventive measures is one of the main methods for reducing the rates of these infections, improving the quality of health care, as well as directing protocols to guide the actions of different health professionals in preventing these problems. The aim of this study is to propose discussions and protocols that establish routines to help control and reduce the number of infections associated with invasive procedures in patients hospitalized in different healthcare settings. To this end, the main scientific findings on the issues raised were analyzed through a descriptive systematic review with a quantitative and qualitative approach, without a time cut-off, using different databases such as Medline and PUBMED. The results identified 98 articles, 38 of which were pre-selected for full-text analysis and 36 were included for analysis in this review. These results confirmed the problem raised, showing that there are many factors that corroborate the increase in systemic infections associated with invasive devices in the healthcare environment. However, professionals can act in the search for a controlled and safe environment, through hygiene actions and the creation of protocols aimed at maintaining safe environments, reducing injuries and infections associated with invasive procedures. DOI: https://doi.org/10.56238/sevened2025.021-055